Accelerated Current Decay Kinetics of a Rare Human Acid-Sensing ion Channel 1a Variant That Is Used in Many Studies as Wild Type - Vaithia, Anand; Vullo, Sabrina; Peng, Zhong; Alijevic, Omar; Kellenberger, Stephan (Frontiers in Molecular Neuroscience, 2019)
Acid-sensing ion channels (ASICs) are neuronal Na+-permeable ion channels that are activated by extracellular acidification and are involved in fear sensing, learning, neurodegeneration after ischemia, and in pain sensation. We have recently found that the human ASIC1a (hASIC1a) wild type clone which has been used by many laboratories in recombinant expression studies contains a point mutation that occurs with a very low frequency in humans. Here we compared the function and expression of ASIC1a wild type and of this rare variant, in which the highly conserved residue Gly212 is substituted by Asp. Residue 212 is located at a subunit interface that undergoes changes during channel activity. We show that the modulation of channel function by commonly used ASIC inhibitors and modulators, and the pH dependence, are the same or only slightly different between hASIC1a-G212 and –D212. hASIC1a-G212 has however a higher current amplitude per surface-expressed channel and considerably slower current decay kinetics than hASIC1a-D212, and its current decay kinetics display a higher dependency on the type of anion present in the extracellular solution. We demonstrate for a number of channel mutants previously characterized in the hASIC1a-D212 background that they have very similar effects in the hASIC1a-G212 background. Taken together, we show that the variant hASIC1a-D212 that has been used as wild type in many studies is in fact a mutant, and that the properties of hASIC1a-D212 and hASIC1a-G212 are sufficiently close that the conclusions made in previous pharmacology and structure-function studies remain valid.